Analisis Program Kampung Keluarga Berencana Perspektif Maqāṣid Al-Syarī’ah (Studi di Kampung Logam Ngingas Waru Sidoarjo Jawa Timur) - Musyafaah, Nur Lailatul (Fakultas Syariah IAIN Purwokerto, 2019)
This article analyzes the programs of family planning village in the Ngingas Waru Village, known as the Kampung Logam (Blacksmith Village), Sidoarjo, East Java in the perspective of maqÄá¹£id al-SyarÄ«'ah (the theory of sharia objectives). In Islamic law, the family planning program is disputed, including the use of contraceptions. The author examines the implementation of the village planning program consisting of Tribina (BKB, BKR, BKL), UPPKS, and PIK-RM, in which they are then analyzed with the concept of maqÄá¹£id al-syarÄ«'ah. The results of the study concludes that the purpose of the formation of the family planning village programs in Ngingas is to improve a prosperous community, both in the fields of religion, health, education, descent, and economy. This concept is in accordance with the objectives of á¸¥if al-mujtamaâ€™ or á¸¥ifáº“ al-ummah in order to protect the rights of citizens related to maintaining the religion, the lives, the consciousness, the lineage, and the wealth.